Efektivitas Pengendalian Penyakit Tungro secara Terpadu dengan Pendekatan Pengendalian Biointensif - Ibrahim, Eli Surya; Mugiasih, Ani; Firmansyah, Firmansyah; Ladja, Fausiah T. (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2021)
Tungro disease is one of the obstacles to increase the national rice productionÂ program. In some areas, this important disease is endemic. On the one hand, some farmers in controlling plant pests and diseases still use pesticides, which negatively impact health and the environment. On the other hand, environmentally friendly tungro disease control technology is available. This study aims to determine an environmentally friendly integrated control technique for tungro disease consisting of resistant varieties, biopesticides, and conservation of natural enemies with flowering plants in suppressing green leafhopper populations and the incidence of tungro transmission in infection-sensitive plant stage.Â The test area is located in Lanrang,Sidrap at the Experimental field of Tungro Disease Research Station, Lanrang Sidrap, South Sulawesi, Indonesia from April to September 2017, using a split-plot design. Main plots are: 1) Biointensive control plots, using flowering plants (refugia) and pest control with andrometa which is a mixture of the entomopathogenic fungus Metharizium anisopliae and sambiloto extract; 2) Conventional plots, without flowering plants and pest control using pesticides. As sub-plots are rice varieties: 1) TN1, 2) IR64, and 3) Inpari-9 Elo which differ in resistance to tungro. Observations were made at 2, 4, 6, and 8 weeks after planting (MST). The results showed that the population of green leafhoppers in the TN1, both in the bio-intensive control plot and in the conventional control plot, was higher than the other two varieties. The population of natural enemies in bio-intensive control consists of 10 predator families and the conventional control consists of 9 predator families. The effectiveness of bio-intensive control has an effect on decreasing the population of green leafhoppers and the diversity of natural enemies, and has no significant effect on the incidence of tungro transmission, and has no effect on grain yield. Therefore, biointensive control needs to be developed to create a pesticide-free agricultural environment.